Legal cynicism, but not depression, mediates the linkbetween adverse environmental factors and youth’s politicalviolence support - Jahnke, Sara (Psychology, crime & law, 2021)
The present work tests mediators of the link between adverse environmental factors and political violence support. Specifically, we investigated if depression and legal cynicism can mediate the association between lack of family cohesion, parental violence, and discrimination on one side and political violence support on the other side. Hypotheses were tested on a large and ethnically diverse dataset of German ninth graders, employing multi-group structural equation modeling. For both genders, we find that lack of family cohesion and parental violence were directly and/or indirectly related to political violence support. While legal cynicism mediated the link between lack of family cohesion and parental violence and political violence support, we found no moderating effect of depression in any of the tested models. These findings indicate that adolescents from dysfunctional families and with cynical attitudes towards legal norms may be at risk to endorse political violence. Prevention efforts that enhance family functioning, social-cognitive abilities, and the internalization of legal norms may deter youth from supporting political violence.